Activation of Peroxisome Proliferator-activated Receptor α (PPARα) Suppresses Hypoxia-inducible Factor-1α (HIF-1α) Signaling in Cancer Cells - Zhou, Jundong (American Society for Biochemistry and Molecular Biology, 2012)
Activation of peroxisome proliferator-activated receptor α (PPARα) has been demonstrated to inhibit tumor growth and angiogenesis, yet the mechanisms behind these actions remain to be characterized. In this study, we examined the effects of PPARα activation on the hypoxia-inducible factor-1α (HIF-1α) signaling pathway in human breast (MCF-7) and ovarian (A2780) cancer cells under hypoxia. Incubation of cancer cells under 1% oxygen for 16 h significantly induced HIF-1α expression and activity as assayed by Western blotting and reporter gene analysis. Treatment of the cells with PPARα agonists, but not a PPARγ agonist, prior to hypoxia diminished hypoxia-induced HIF-1α expression and activity, and addition of a PPARα antagonist attenuated the suppression of HIF-1α signaling. Activation of PPARα attenuated hypoxia-induced HA-tagged HIF-1α protein expression without affecting the HA-tagged HIF-1α mutant protein level, indicating that PPARα activation promotes HIF-1α degradation in these cells. This was further confirmed using proteasome inhibitors, which reversed PPARα-mediated suppression of HIF-1α expression under hypoxia. Using the co-immunoprecipitation technique, we found that activation of PPARα enhances the binding of HIF-1α to von Hippel-Lindau tumor suppressor (pVHL), a protein known to mediate HIF-1α degradation through the ubiquitin-proteasome pathway. Following PPARα-mediated suppression of HIF-1α signaling, VEGF secretion from the cancer cells was significantly reduced, and tube formation by endothelial cells was dramatically impaired. Taken together, these findings demonstrate for the first time that activation of PPARα suppresses hypoxia-induced HIF-1α signaling in cancer cells, providing novel insight into the anticancer properties of PPARα agonists.